2011
DOI: 10.1136/ard.2011.151464
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance, insulin sensitivity and  -cell function in patients with rheumatoid arthritis treated with or without low-to-medium dose glucocorticoids

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
2
14

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 28 publications
9
69
2
14
Order By: Relevance
“…In our study, short-term prednisolone exposure did not aggravate the already present severe insulin resistance. Similarly, in a previous study, chronic GC treatment in patients with rheumatoid arthritis did not further decrease insulin sensitivity compared with patients without GC-use (39).…”
Section: Clinical Study R E Van Genugten and Othersmentioning
confidence: 99%
“…In our study, short-term prednisolone exposure did not aggravate the already present severe insulin resistance. Similarly, in a previous study, chronic GC treatment in patients with rheumatoid arthritis did not further decrease insulin sensitivity compared with patients without GC-use (39).…”
Section: Clinical Study R E Van Genugten and Othersmentioning
confidence: 99%
“…As already described, RA patients tend to have decreased insulin sensitivity and impaired b-cell function when compared to control subjects of comparable age with normal glucose tolerance. Low doses of prednisolone have been shown to acutely affect carbohydrate metabolism [117] and GC-induced hyperglycemia is common in individuals with or without diabetes [114]. However, within the context of RA, the long-term effects of low-dose GC are not clear and longitudinal studies are required in this area.…”
Section: Effects Of Gcs On Glycaemiamentioning
confidence: 99%
“…The mechanisms underlying the effect remain poorly understood, but appear to include increases in gluconeogenesis and hepatic glucose output, as well as inducing insulin resistance [116]. In a cross-sectional analysis of patients with established RA and without type 2 diabetes mellitus, tests showed that there was no difference between chronic GC users and GCnaïve patients in terms of glucose tolerance, insulin sensitivity and b-cell function [117]. As already described, RA patients tend to have decreased insulin sensitivity and impaired b-cell function when compared to control subjects of comparable age with normal glucose tolerance.…”
Section: Effects Of Gcs On Glycaemiamentioning
confidence: 99%
“…The principal rationale for this treatment regimen is to achieve a higher therapeutic effect than that achieved with conventional oral steroid doses, while minimizing toxicity (4).…”
Section: To the Editormentioning
confidence: 99%